MANAJEMEN PENDIDIKAN KARAKTER DI POLITEKNIK AL ISLAM DAN UNIVERSITAS ISLAM NEGERI SUNAN GUNUNG DJATI BANDUNG: Management of Character Education at Al Islam Polytechnic and State Islamic University of Sunan Gunung Djati Bandung - karmilah karmilah (JURNAL TERAS KESEHATAN, 2021)
The number of juvenile delinquency cases in Indonesia today ranging from brawls, promiscuity, drugs, and so on has become the author's interest to determine the extent to which character education implementation education has been carried out in several universities in Bandung. This research approach used a qualitative approach with a case study method that observes the sustainability of character education programs at UIN Bandung and Politeknik Al Islam Bandung. Techniques for collecting data through interviews, observations, and documentation. The result showed that that the management of character education program from two tertiary institutions has been running well both with the existence of annual programs, strategic plans and annual final reports to the relevant parties. The supporting factors of the two tertiary institutions were almost the same, namely, the two universities have a religious atmosphere that was thick with Islamic norms and even with almost the same inhibiting factors, namely the development of globalization flows that influenced character development. In order for character education to produce quality graduates in accordance with existing standards and indicators, the authors need to recommend several things, 1) must understand the nature of character education 2) There was involvement of all parties 3) Need for supporting facilities and infrastructure 4) Need communication between the institution and